LITERARY TRANSLATION AND CULTURAL IDENTITY. (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation: This article explores the intricate relationship between literary translation and cultural identity. By examining the ways in which translation shapes and is shaped by cultural contexts, the paper highlights the dual role of translators as mediators and creators of cultural identity. The study also delves into the methodological approaches used in literary translation, analyzing the impact of these methods on the preservation or transformation of cultural identity within translated texts.